62 Prolonged, Intermittent Monitoring using a Handheld ECG Significantly Increases the Diagnostic Yield of Paroxysmal Atrial Fibrillation. (6th June 2015) - Howlett, Philippa; Mahmoudi, Michael; Morritt, Jennie; Greswell, Laura; Jabr, Rita; Fry, Chris; Leatham, Edward
Abstract : Purpose: Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia. Paroxysmal AF (PAF) comprises approximately half of AF cases and poses an equivalent risk of thromboembolism to other AF sub-types. However, PAF poses a particular diagnostic challenge given its variable frequency, potential brevity and frequent lack of symptoms. Currently, no definitive method to identify PAF has been proposed although 24-hour or 1-week rhythm monitoring remain common practice. We aim to determine whether the longer-term, intermittent use of a handheld ECG monitor is an effective investigational tool to improve the diagnosis of PAF in a targeted population. Methods: Patients meeting the following criteria were entered into the study: suspected paroxysmal atrial arrhythmia (defined as palpitations or detection of an irregular pulse); aged 40 years and over; no previously documented atrial arrhythmia; sinus rhythm confirmed with a 12-lead ECG; no significant electrolyte disturbance. Participants were issued with an automated cardiac event recorder for 1-week, deemed standard practice (R Test Evolution 4, Novacor). They also used a handheld ECG monitor (OMRON Portable ECG Monitor HCG-801), recording 30-second segments twice-daily and with relevant symptoms, for a 12-week period. Recordings were analysed by a blinded cardiologist. Results: We recruited 110 consecutive eligible participants (mean age 66 years; 70% female). 84% were referred with palpitations and 16% with an irregular pulse. 90% of participants completed the study and 99% of recordings were suitable for analysis. Atrial arrhythmias were detected in 29 patients (26%). Of these 23 were diagnosed with PAF, 5 with atrial flutter and 1 with atrial tachycardia. This group had a mean CHA2 DS2 VASc score of 2.1. 31% of cases were identified using the standard device, 41% using the handheld ECG monitor (p = 0.72) and 28% with both devices. A significantly greater number of atrial arrhythmias were detected over a 12-week monitoring period as compared to both a 24-hour (n = 29 vs 5, p = 0.0001) and 1-week monitoring period (n = 29 vs 17, p = 0.03); see Figure 1 . Conclusions: The intermittent use of a handheld ECG monitor over 12-weeks significantly increases the diagnostic yield of PAF when compared to standard investigation. Our findings suggest that the duration of cardiac monitoring used in current practice should be extended.